Continuous Development of Knowledge Management for Higher Education Institutions - Ming-Chang Wu; Didik Nurhadi (Teknologi dan Kejuruan: Jurnal Teknologi, Kejuruan, dan Pengajarannya, 2019)
Higher educational institutions play a very important role in gaining, improving, using, supplying, and storing knowledge and making it available for their students. For the sake of the institutions, such information needs to be managed properly and constantly. The aim of this paper is to describe how to establish effective knowledge management so that it can bring maximum benefit for all academicians. For this purpose, higher educational institutions need to know the definition of knowledge management, its structure and role model, the way of obtaining innovation from it, the use of it. Understanding all mentioned makes it easier for them to manage knowledge and come up with constant innovations through an academic research which will reveal result information, innovative ideas, and data of innovation developed. The success of knowledge management program depends on three components, human resources, the management processes, and existing technology adopted in the institutions.